2022
DOI: 10.3389/fpsyt.2022.819704
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Correlates of Internet Addiction Symptoms and Their Association With Quality of Life in Adolescents With Major Depressive Disorder: A Multicenter Cross-Sectional Study

Abstract: BackgroundInternet addiction (IA) symptoms are common among adolescents and negatively impact their academic performance and development. These symptoms are also associated with lower quality of life (QOL) and increased suicidality. This study aimed to examine the prevalence and the sociodemographic and clinical correlates of IA symptoms in adolescents with major depressive disorder (MDD) and their association with QOL.MethodsThis cross-sectional study was conducted in three general and four psychiatric hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…According to the criteria, 20-49 points are normal, and ≥ 50 points are mild to severe IA [ 42 , 43 ]. Its Chinese version has good reliability and validity and Cronbach’s α coefficient was 0.90 [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the criteria, 20-49 points are normal, and ≥ 50 points are mild to severe IA [ 42 , 43 ]. Its Chinese version has good reliability and validity and Cronbach’s α coefficient was 0.90 [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the criteria, 20-49 points are normal, and ≥ 50 points are mild to severe IA [29,30]. Its Chinese version has good reliability and validity [31].…”
Section: Young's Internet Addiction Test (Iat)mentioning
confidence: 99%
“…Studies have shown that the prevalence of Internet addiction has increased in recent years from 3% to 26.8% in countries like Hong Kong and 46.8% in provinces of China. [ 4 5 ] Many experts attribute the main causes of PIU to excessive internet usage or the misuse of certain internet functions. A related terminology more widely used is Internet addiction (IA), which has been described as the usage of the Internet more than 12 h a week or the usage of the Internet to impair daily functioning.…”
Section: Introductionmentioning
confidence: 99%